Transcriptomic landscape of prophase I sunflower male meiocytes - Flórez-Zapata, Nathalia M. V.; Reyes-Valdés, M. H.; Hernandez-Godínez, Fernando; Martínez, Octavio (Frontiers in Plant Science, 2014)
Meiosis is a form of specialized cell division that generates gametes, allowing recombination of alleles and halving the chromosome number. Arabidopsis and maize are the plant models that have been most extensively studied to determine the genes involved in meiosis. Here we present an RNA-seq study in which gene expression in male meiocytes isolated during prophase I was compared to that in somatic tissues of the sunflower HA89 line. We sampled more than 490 million gene tags from these libraries, assembled them de novo into a sunflower transcriptome. We obtained expression data for 36,304 sunflower genes, of which 19,574 (54%) were differentially expressed between meiocytes and somatic tissue. We also determined the functional categories and metabolic pathways that are differentially expressed in these libraries. As expected, we found large differences between the meiotic and somatic transcriptomes, which is in accordance with previous studies in Arabidopsis and maize. Furthermore, most of the previously implicated meiotic genes were abundantly and differentially expressed in meiocytes and a large repertoire of transcription factors and genes related to silencing are expressed in the sunflower meiocytes. We detected transcription factors which appear to be exclusively expressed in meiocytes. Our results allow for a better understanding of the conservation and differences in the meiotic transcriptome of plants.